Professional Competence Development of Teaching Staff in Higher Education Institutions under Martial Law - Vaintraub, Mark (Educational Challenges, 2024)
The purpose of this article is to show the problems of professional competence development of higher-education teaching staff under martial law. The relevance and necessity of developing teachers’ professional competence focused on specific requirements and challenges, in particular in the conditions of martial law, is emphasized.Methodology. In the research process, general scientific and pedagogical research methods were used, basically theoretical ones: analysis, synthesis, classification, systematization, and generalization.Results. Among the specific components of the professional competence of teachers under conditions of martial law, the following are identified: safety of life, health, and labor protection; rules and behavior in emergency situations during war; adaptation of educational programs; ability for crisis management of the educational process and of teaching students; teaching in extraordinary conditions; moral, emotional, and psychological support of colleagues and students in stressful situations; effective use of information and digital technologies; ability to organize inclusive education with students with special educational needs; personal qualities (courage, resilience, patriotism, dedication to one’s students and studies, the ability to introduce classes in conditions of instability and promote a strong spirit among students); and cooperation with the military armed forces of Ukraine, police, administration, humanitarian organizations, stakeholders, etc.Conclusions. The model of professional competence development of teaching staff in higher education institutions under martial law is developed in the form of a graph. Some components of this model are reviewed. The result of the developed model will make it possible to provide higher quality and safer education in difficult conditions, in particular in the fields of professional and technological education.
Keywords: Martial Law; Higher Education Institutions; Teaching Staff; Professional Competence